Building a 3D game with LibGDX : learn how to build an exciting 3D game with LibGDX from scratch - Di Giuseppe, Sebastián; Krühlmann, Andreas; Rijnswou, Elmar van (Community experience distilled., 2016)
Learn how to build an exciting 3D game with LibGDX from scratch About This Book Implement an exhaustive list of features that LibGDX unleashes to build your 3D game. Write, test, and debug your application on your desktop and deploy them on multiple platforms. Gain a clear understanding of the physics behind LibGDX and libraries like OpenGL and WebGL that make up LibGDX. Who This Book Is For If you are a game developer or enthusiasts who want to build 3D games with LibGDX, then this book is for you. A basic knowledge of LibGDX and Java programming is appreciated. What You Will Learn Learn the potential of LibGDX in game development Understand the LibGDX architecture and explore platform limitation and variations Explore the various approaches for game development using LibGDX Learn about the common mistakes and possible solutions of development Discover the 3D workflow with Blender and how it works with LibGDX Implement 3D models along with textures and animations into your games Familiarize yourself with Scene2D and its potential to boost your game's design In Detail LibGDX is a hugely popular open source, cross-platform, Java-based game development framework built for the demands of cross-platform game development. This book will teach readers how the LibGDX framework uses its 3D rendering API with the OpenGL wrapper, in combination with Bullet Physics, 3D Particles, and Shaders to develop and deploy a game application to different platforms You will start off with the basic Intellij environment, workflow and set up a LibGDX project with necessary APIs for 3D development. You will then go through LibGDX's 3D rendering API main features and talk about the camera used for 3D. Our next step is to put everything together to build a basic 3D game with Shapes, including basic gameplay mechanics and basic UI. Next you will go through modeling, rigging, and animation in Blender. We will then talk about refining mechanics, new input implementations, implementing enemy 3D models, mechanics, and gameplay balancing. The later part of this title will help you to manage secondary resources like audio, music and add 3D particles in the game to make the game more realistic. You will finally test and deploy the app on a multitude of different platforms, ready to start developing your own titles how you want! Style and approach A step by step guide on building a 3D game with LibGDX and implementing an exhaustive list of features that you would wish to incorpo...